Waxy Phenotype Evolution in the Allotetraploid Cereal Broomcorn Millet: Mutations at the GBSSI Locus in Their Functional and Phylogenetic Context - Hunt, Harriet V. (Oxford University Press, 2013)
Waxy mutants, in which endosperm starch contains ∼100% amylopectin rather than the wild-type composition of ∼70% amylopectin and ∼30% amylose, occur in many domesticated cereals. The cultivation of waxy varieties is concentrated in east Asia, where there is a culinary preference for glutinous-textured foods that may have developed from ancient food processing traditions. The waxy phenotype results from mutations in the GBSSI gene, which catalyzes amylose synthesis. Broomcorn or proso millet (Panicum miliaceum L.) is one of the world’s oldest cultivated cereals, which spread across Eurasia early in prehistory. Recent phylogeographic analysis has shown strong genetic structuring that likely reflects ancient expansion patterns. Broomcorn millet is highly unusual in being an allotetraploid cereal with fully waxy varieties. Previous work characterized two homeologous GBSSI loci, with multiple alleles at each, but could not determine whether both loci contributed to GBSSI function. We first tested the relative contribution of the two GBSSI loci to amylose synthesis and second tested the association between GBSSI alleles and phylogeographic structure inferred from simple sequence repeats (SSRs). We evaluated the phenotype of all known GBSSI genotypes in broomcorn millet by assaying starch composition and protein function. The results showed that the GBSSI-S locus is the major locus controlling endosperm amylose content, and the GBSSI-L locus has strongly reduced synthesis capacity. We genotyped 178 individuals from landraces from across Eurasia for the 2 GBSSI and 16 SSR loci and analyzed phylogeographic structuring and the geographic and phylogenetic distribution of GBSSI alleles. We found that GBSSI alleles have distinct spatial distributions and strong associations with particular genetic clusters defined by SSRs. The combination of alleles that results in a partially waxy phenotype does not exist in landrace populations. Our data suggest that broomcorn millet is a system in the process of becoming diploidized for the GBSSI locus responsible for grain amylose. Mutant alleles show some exchange between genetic groups, which was favored by selection for the waxy phenotype in particular regions. Partially waxy phenotypes were probably selected against—this unexpected finding shows that better understanding is needed of the human biology of this phenomenon that distinguishes cereal use in eastern and western cultures.